GANENAN, PAWON, DAN DIENG CULTURE FESTIVAL: MEDIA INTERAKSI DAN PARTISIPASI MASYARAKAT DALAM PARIWISATA DIENG - Nursaid, Dede; Muhadli, Rahmat Aminullah; Zurinani, Siti (Studi Budaya Nusantara, 2022)
Dieng Kulon is a potential tourism village that attracts tourists. In addition to their tourism potential, the Dieng people have traditions and culture: ruwatan, ganenan, and pawon. Ruwatan is a Dieng “rambut gimbal” shaving procession. Children in Dieng who have dreadlocks are the chosen children and the incarnation of Kyai Kolodete (Dieng's ancestor). This Ruwatan, which was later managed by the Pokdarwis Dieng Pandawa, became an annual cultural festival called the Dieng Culture Festival. The results of this study are that the Dieng Culture Festival provides benefits to the local community because the tourism industry in Dieng Kulon is starting to be managed properly. The management uses the community based tourism method brought by Pokdarwis Dieng Pandawa and is implemented in the development of Dieng tourism. The CBT method is considered to have been successfully implemented, although not completely because some people are still refused to participate in Dieng tourism. Stakeholders consisting of several actors collaborate and participate. In CBT there are dimensions that need to be produced, namely the economic dimension, social dimension, political dimension, cultural dimension, and environmental dimension. These five dimensions can be seen through the process and method of the Dieng Pandawa Pokdarwis implementing CBT in Dieng tourism. Ganenan and pawon are a local community tradition to warm the body and a way for the community to strengthen interaction. From this, how the culture and traditions in the community are managed by the Pokdarwis Dieng Pandawa with the concept of CBT so that community participation is the main point. Community participation is the main gate of tourism development with the CBT concept.